Edge indentation of ice with a displacement-controlled oscillating cylindrical structure - Hendrikse, Hayo; Metrikine, Andrei (Cold regions science and technology, 2016)
Indentation tests were performed with a cylindrical structure subject to a controlled harmonic oscillation. The aim of the experiments is to study ice behaviour when loaded at a varying rate of indentation closely resembling that during frequency lock-in. Focus of the experiments is on the development of the global load, local pressure and contact area during indentation. To this end, a tactile sensor is installed at the ice–structure interface which allows for detailed measurement of these quantities. During the experiment the frequency and amplitude of structural oscillation were varied, as well as the indentation velocity. Results show that ice behaviour changes from brittle to transitional, and ultimately to ductile, as the relative velocity between ice and structure decreases during a cycle of oscillation. Both transitional and ductile behaviour result in an increase of the maximum global ice load upon fracture. The obtained increase in maximum global load depends on the duration of ductile behaviour of the ice. The longer the duration, the greater the increase in maximum global load compared to peak loads in the brittle regime. Tactile sensor measurements indicate that the increase in global load occurs as a result of a combined increase in contact area and mean contact pressure. The obtained results provide insight into the parameters influencing the occurrence of frequency lock-in of structures interacting with level ice. •A forced vibration test setup for controlled dynamic fracture of ice is presented.•Results on contact area, local pressure and global load are reported.•A dependence of the increase in global load on duration of ductile behaviour is obtained.•Parameters of fundamental influence on frequency lock-in are suggested.